Prior renovascular hypertension does not predispose to atherosclerosis in mice. (June 2016) - Mortensen, Martin Bødtker; Nilsson, Line; Larsen, Tore G.; Espeseth, Eirild; Bek, Marie; Bjørklund, Martin M.; Hagensen, Mette K.; Wolff, Anne; Gunnersen, Stine; Füchtbauer, Ernst-Martin; Boedtkjer, Ebbe; Bentzon, Jacob F.
Abstract: Background: Hypertension is a major risk factor for development of atherosclerotic cardiovascular disease (ASCVD). Although lowering blood pressure with antihypertensive drugs reduces the increased risk of ASCVD, residual increased risk still remains, suggesting that hypertension may cause chronic changes that promote atherosclerosis. Thus, we tested the hypothesis that hypertension increases the susceptibility to atherosclerosis in mice even after a period of re-established normotension. Methods: We used the 2-kidney, 1-clip (2K1C) technique to induce angiotensin-driven renovascular hypertension, and overexpression of the proprotein convertase subtilisin/kexin type 9 (PCSK9) gene to cause severe hypercholesterolemia and atherosclerosis. Results: First, we performed 2K1C (n = 8) or sham surgery (n = 9) in PCSK9 transgenic mice before they were fed a high fat diet for 14 weeks. As expected, 2K1C did not affect cholesterol levels, but induced cardiac hypertrophy and significantly increased the atherosclerotic lesion area compared to sham mice (1.8 fold, p < 0.01). Next, we performed 2K1C (n = 13) or sham surgery (n = 14) in wild-type mice but removed the clipped/sham-operated kidney after 10 weeks to eliminate hypertension, and subsequently induced hypercholesterolemia by way of adeno-associated virus-mediated hepatic gene transfer of PCSK9 combined with high-fat diet. After 14 weeks of hypercholesterolemia, atherosclerotic lesion areas were not significantly different in mice with or without prior 2K1C hypertension (0.95 fold, p = 0.35). Conclusion: Renovascular hypertension in mice does not induce pro-atherogenic changes that persist beyond the hypertensive phase. These results indicate that hypertension only promotes atherogenesis when coinciding temporally with hypercholesterolemia. Highlights: Prior hypertension strongly promotes risk of atherosclerotic cardiovascular disease. We tested if prior hypertension increases atherosclerosis development in mice. We found that prior hypertension does not increase atherosclerosis development. Hypertension only promotes atherogenesis when coinciding with hypercholesterolemia.